ASSOCIATION BETWEEN AUTONOMIC REACTIVITY INDICES AND SERUM NT-PROBNP LEVELS, ENDOTHELIAL DYSFUNCTION MARKERS, AND 25-HYDROXYVITAMIN D (25(OH)D) LEVEL IN PREGNANT WOMEN WITH HYPERTENSIVE DISORDERS OF PREGNANCY - Zadorozhniy, Ya.S.; Ostafiichuk, S.O.; Drohomyretska, N.V.; Kravchuk, I.V.; Motsyuk, Yu.B.; Bielinskyi, M.V.; Herashchenko, A.S. (World of Medicine and Biology, 2025)
Hypertensive disorders of pregnancy are increasingly recognized as multifactorial conditions involving autonomic imbalance, endothelial dysfunction, and vitamin D deficiency. This study evaluated the effects of a comprehensive multidisciplinary intervention – including psychological support, autonomic regulation strategies, and targeted supplementation – on heart rate variability, endothelial markers, and vitamin D status in pregnant women with hypertensive disorders of pregnancy. A total of 124 patients with hypertensive disorders of pregnancy and 35 healthy controls were enrolled. Compared to controls, women with hypertensive disorders of pregnancy exhibited significantly lower heart rate variability parameters, higher levels of N-terminal pro-brain natriuretic peptide and endothelin-1, reduced nitric oxide, and lower 25-hydroxyvitamin D concentrations. The intervention group demonstrated significant improvements in autonomic function and endothelial biomarkers after treatment, with increased standard deviation of NN intervals, root mean square of successive differences, percentage of successive NN intervals differing by more than 50 milliseconds, and decreased low-frequency to high-frequency ratio. These findings support the effectiveness of a multidisciplinary approach in mitigating autonomic and vascular dysfunction in hypertensive disorders of pregnancy.